Bolted Joint Loosening Analysis Due to Structural Vibrations using Short-Time Fourier Transform and Wavelet Transform - Rahmatsyah Maksum Ramsi; Meifal Rusli; Feblil Huda (METAL: Jurnal Sistem Mekanik dan Termal, 2025)
This research investigates the influence of bolt loosening on the dynamic behavior of a steel beam structure under continuous vibration excitation for 30 minutes. Bolted joints play a critical role in maintaining structural integrity; however, loosening caused by vibration remains one of the most common failure mechanisms in mechanical structures. To capture the effect of bolt loosening, acceleration responses were analyzed using time-domain inspection, Fast Fourier Transform (FFT), Short-Time Fourier Transform (STFT), and Continuous Wavelet Transform (CWT). The experimental setup involved controlled vibration excitation applied to a steel beam with bolted connections, and response signals were recorded at different stages of loosening progression. The time-domain analysis showed a gradual reduction in acceleration amplitude as bolt tightness decreased, indicating energy dissipation and stiffness loss. FFT provided an overview of frequency content but lacked sensitivity to localized variations. STFT and CWT enabled a more detailed examination of the time-frequency domain, revealing a loss of high-frequency components and significant redistribution of energy patterns during the loosening process. Both methods successfully identified shifts in natural frequencies and variations in response amplitude. Especially, CWT exhibited superior resolution in detecting early-stage loosening compared to STFT, making it more effective for practical monitoring applications. These results highlight the potential of time-frequency analysis as a diagnostic tool for vibration-based Structural Health Monitoring (SHM) systems. Early detection of bolt loosening through non-destructive vibration analysis can improve safety, reduce maintenance costs, and extend the service life of mechanical structures.